How substandard dwellings and housing affordability problems are associated with poor health in a vulnerable population during the economic recession of the late 2000s. Issue 1 (December 2015) - Novoa, Ana; Ward, Julia; Malmusi, Davide; Díaz, Fernando; Darnell, Mercè; Trilla, Carme; Bosch, Jordi; Borrell, Carme
Abstract Introduction Given the increasing number of people in Spain struggling to pay housing-related costs during the economic recession, it is important to assess the health status of these communities as compared to the general population and to better understand the different housing dimensions that are related with poor mental health. This study aims to describe the housing conditions and health status of a sample of people assisted by Caritas Barcelona (Spain) and living in inadequate housing and/or struggling to pay their rent or mortgage, to compare the health outcomes of this population with those of the overall population of Barcelona, and to analyze the association between housing dimensions and mental health. Methods We used a cross-sectional design. The participating adults (n = 320) and children (n = 177) were those living in the dioceses of Barcelona, Sant Feliu and Terrassa (Spain) in 2012 and assisted by Cáritas. They were asked to answer to three questionnaires on housing and health conditions. Eight health related variables were used to compare participants with Barcelona's residents and associations between housing conditions and poor mental health were examined with multivariate logistic regression models. Results In Barcelona, people seeking Caritas's help and facing serious housing problems had a much poorer health status than the general population, even when compared to those belonging to the most deprived social classes. For example, 69.4 % of adult participants had poor mental health compared to 11.5 % male and 15.2 % female Barcelona residents. Moreover, housing conditions were associated with poor mental health. Conclusions This study has shown how, in a country hit by the financial recession, those people facing housing problems have much worse health compared to the general population.